Towards a new application of amaranth seed oil as an agent against Candida albicans. Issue 22 (18th November 2021) - De Vita, Daniela; Messore, Antonella; Toniolo, Chiara; Frezza, Claudio; Scipione, Luigi; Bertea, Cinzia Margherita; Micera, Marco; Di Sarno, Veronica; Madia, Valentina Noemi; Pindinello, Ivano; Roscilli, Patrizia; Botto, Alfonso; et al.
Abstract: Amaranthu s spp. (Amaranthaceae family), known as amaranth, are plants native of Central America, today produced in many parts of the world. due to their popularity popular as a health food. Because of its composition, amaranth can be considered to be attractive not only as a food but also for pharmaceutical and cosmetics uses. To date, antifungal activity of amaranth extracts has not been totally investigated, therefore the scope of this study was to evaluate the antifungal effect of the apolar fraction from Amaranthus cruentus L. seeds extract, alone and in association with antifungal drugs terbinafine, a common antifungal agent, which itself has only fungistatic effect on Candida albicans strains without exerting fungicidal activity. Our results demonstrate that this amaranth oil in combination with terbinafine has synergic fungistatic and fungicidal activity, with FICI of 0.466 and 0.496, respectively. No fungistatic and fungicidal activity of terbinafine alone at concentrations up to 64 μg/mL and amaranth oil alone at concentrations up to 2000 μg/mL, against all tested C. albicans strains, were observed. does not show activity towards Candida albicans strains but it can effectively potentiate the antifungal activity of terbinafine, a common antifungal agent which itself This result suggests the possible application of amaranth oil in the preparation of formulations with terbinafine for topical use. Graphical Abstract: